(untitled) (Research, Society and Development, 2024)
Objective: To identify the actions developed by primary care health professionals in the context of men’s health in the municipality of Santo Cristo/RS; understand the potentialities/difficulties in implementing the human policy by primary care health professionals. Methodology: qualitative study of a descriptive and exploratory nature, carried out with five health professionals from a small municipality in the northwest of Rio Grande do Sul. For data collection, carried out in the basic health unit where they work, we used of a semi-structured interview, with the aid of a recorder. Results and discussion: health professionals reported specific health actions related mainly to prostate cancer. Difficulties were reported in capturing these men, who demonstrate prejudice, fear and resistance regarding understanding the importance of taking care of their own health. Considerations: it is believed that it is essential that management gets involved in the process, trains professionals and seeks creative alternatives so that this population emerges from invisibility. Furthermore, the need to implement actions based on PNAISH is emphasized, both in terms of prevention and promotion and health recovery, taking into account already chronic health processes.